Optimal Distributed Interference Mitigation for Small Cell Networks With Non-Orthogonal Multiple Access: A Locally Cooperative Game - Wang, Xianling; Zhang, Haijun; Tian, Yue; Zhu, Chen; Leung, Victor C. M. (IEEE access, 2018)
In this paper, we study the potential of non-orthogonal multiple access (NOMA) for the purpose of interference mitigation in downlink small cell networks (SCNs). Different from prior works, we focus on opportunistically multiplexing different users on the same subchannel to avoid the severe inter-cell interference brought in by ultradense networking. Aiming to maximize the network throughput, we formulate a distributed subchannel assignment problem with local information exchange. This problem is analyzed through a locally cooperative game model, and the existence of Nash equilibrium (NE) is confirmed by proving that the formulated game is an exact potential game. To solve the problem, we design two concurrent distributed algorithms based on best response (BR) and spatial adaptive play (SAP), respectively. The BR-based algorithm guarantees rapid convergence to an NE, which may not be globally optimal. On the contrary, the SAP-based algorithm can find the global optimum with an arbitrary large probability, although the learning process requires more iterations to converge. Simulation results reveal that the aggregate interference can be more efficiently suppressed in NOMA enhanced networks, which can lead to higher network throughputs. Besides, the superiority of NOMA over orthogonal multiple access is more obvious when the network grows denser.